CONTROL OF THERMOTECHNICAL PROCESS TAKING INTO ACCOUNT THERMAL-STRESSES - N. P. Voronova; G. A. Klimovich (Литьë и металлургия)
The methods of calculation of maximal tension srtesses arising in slat at asymmetric heating are set out. The liminations on magnitude of heat flow and temperature of heating environment for initial period of heating and on regular stage of the process are formulated. The ojfered methods allow by means of variation of the heat-exchange coefficient value on the surface of slat to determine the thermal regime of heating excluding the possibility of exceeding of allowable level of thermal stresses in the heated article and arising of defects.